Pengaruh Disiplin Kerja, Kepuasan Kerja, Lingkungan Kerja, Dan Profesionalisme Terhadap Kinerja Perangkat Desa Banjarrejo Kec.Batanghari Kab.Lampung Timur - Aulia, Fitri Anul; Ratmono, Ratmono (Universitas Muhammadiyah Metro, 2022)
This study aims to determine whether there is an influence between work discipline, job satisfaction, work environment, and professionalism on the performance of the Banjarrejo Village apparatus, Kec. Batanghari. From these problems, this study aims to determine the effect of work discipline, job satisfaction, work environment, and professionalism on the performance of the Banjarrejo Village apparatus, Kec. Batanghari, East Lampung Regency. The population in this research is all the apparatus of Banjarrejo Village, Kec. Batanghari totaling 45 people using saturated samples so that all populations are sampled. The research method used is quantitative with data analysis techniques using multiple linear regression test, hypothesis testing and testing the coefficient of determination with the help of SPSS. Based on the results of the research that has been done, it can be concluded that work discipline, job satisfaction, work environment, and professionalism simultaneously have a positive and significant effect on the performance of the Banjarrejo Village apparatus, Kec. Batanghari. Keywords: Work Discipline, Job Satisfaction, Work Environment, Professionalism, Performance